PENDAMPINGAN PEMBUATAN ALAT PERMAINAN EDUKATIF DARI POTENSI SUMBER DAYA ALAM - Al khudri Sembiring; Sriwahyuni Sriwahyuni; Sean Marta Efastri (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2017)
Limitations of operational funds that are often experienced by PAUD resulted in insufficient availability of game equipment to be equivalent to the number of students. After direct interviews, the facts were collected based on information from the managers of both PAUD and field observations including: Playground for children, Educational Game Tools (APE) is not sufficient and meet the needs of every child so that the competition between children often occurs for can play available APE. Lack of APE tried to be overcome by making their own but educators do not have the expertise and experience sufficient to utilize the materials from nature as a source of raw materials making APE useful as a medium of learning for children. This devotional activity aims to develop the competence of PAUD educators in the process of making educational game tools that use raw materials from the potential of natural resources available around PAUD institutions. This activity is held for one day in PAUD Berkah cheerful Tenayan Raya with the number of participants as many as 20 PAUD teachers in Tenayan Raya District. Based on the results of data analysis obtained can be concluded that the knowledge and skills of teachers in making educational game equipment after the socialization has increased. This is reflected in the increased percentage of teachers' knowledge and skills in making educative game tools from natural raw materials.